El impacto del servicio al cliente sobre la perdurabilidad empresarial en los bares del Cercado de Lima - Contreras Galarza, Renzo Evgueni Daniel (2023)
Customers, for an organization, represent one of the most important assets, especially if it is in the service area and, as far as it is concerned, it is important to try to keep them with the organization and achieve their loyalty with the company. To achieve this goal, the company must try to meet the needs of customers and exceed their expectations in order to maintain competition in the market. However, how can an organization keep customers satisfied and at the same time maintain competitive in the environment where it is located? For this purpose, the following research work will relate the independent variable "Customer Service" with the dependent variable "Business Durability" to answer our question: how does customer service generate factors of business durability in bars from Cercado de Lima district? The importance of the following research lies in the need for investors, entrepreneurs and new entrepreneurs to know the situation in which the market is in the area in which they want to enter and know the ways and ways in which their current or new companies may remain competitive in a market that is constantly changing. The main input for economic sciences and business focuses on granting knowledge of the factors that can give organizations or companies the ability to remain in the market and the options for changes and improvements they can make to satisfy their customers.